Phenomenological-Hermeneutical Approach to Borderline Personality Disorder - Cristóbal Pacheco; FOSSA ARCILA, PABLO SEBASTIAN (Emerald Publishing Limited, 2025)
Phenomenological Approach to Borderline Personality Disorder explores the subjective experience of individuals with borderline personality disorder (BPD) through the lens of phenomenology and hermeneutics. This book bridges the gap between theoretical psychology and lived experience, offering a nuanced understanding of emotional instability, relational struggles, and the profound challenges faced by those living with BPD. By integrating methodologies such as interpretative phenomenological analysis (IPA) and micro-phenomenological analysis, the authors present a comprehensive framework that uncovers the intricate dynamics of BPD. Dr. Cristóbal Pacheco and Dr. Pablo Fossa illuminate BPD from multiple dimensions, addressing the instability inherent to this condition, the temporo-spatial elements of chaotic emotions, and the role of empathy in understanding subjective realities. The book also delves into hermeneutics as a pathway to interpret and uncover deeper meanings, inviting readers to see BPD as not just a diagnosis but as a multifaceted human experience. This book is an essential resource for psychologists, clinicians, researchers, and students seeking a deeper comprehension of BPD, as well as for those interested in phenomenology and hermeneutics. It challenges conventional paradigms by prioritizing the lived realities of individuals, promoting a more empathetic and holistic approach to mental health care.